2012
DOI: 10.1093/ntr/nts172
|View full text |Cite
|
Sign up to set email alerts
|

Nornicotine Nitrosation in Saliva and Its Relation to Endogenous Synthesis of N'-Nitrosonornicotine in Humans

Abstract: Our results demonstrate that NNN can be formed from nornicotine in human saliva without deliberate addition of any other substance. Therefore, nornicotine, as present in tobacco or in nicotine replacement products, is a carcinogen precursor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 23 publications
3
43
0
Order By: Relevance
“…7 This is believed to occur by endogenous nitrosation of nornicotine, a metabolite of nicotine which is easily converted to NNN by reaction with salivary nitrite, or with nitrite under the favorable conditions of gastric pH. 47 …”
Section: Biomarkers Of Exposurementioning
confidence: 99%
“…7 This is believed to occur by endogenous nitrosation of nornicotine, a metabolite of nicotine which is easily converted to NNN by reaction with salivary nitrite, or with nitrite under the favorable conditions of gastric pH. 47 …”
Section: Biomarkers Of Exposurementioning
confidence: 99%
“…NNN is also present in smoke from cigars and cigarettes, in the saliva of people who chew betel quid with tobacco, and in the saliva of oral-snuff users (19). There is great variation in levels of NNN and NNK in mainstream smoke of cigarettes.…”
Section: Biomarkers Associated With Tobacco Smokingmentioning
confidence: 99%
“…This is particularly important when the precursor amine in question – in this case nornicotine - is readily nitrosated as we have shown in our previous studies [20;21], and when the expected amounts of nitrosamine detected - in this case NNN - may be quite low, as in e-cigarette users. Our initial unpublished analyses of the urine of e-cigarette users showed sporadic, poorly reproducible, and relatively low levels of total NNN, which we attribute to uncontrolled artifact formation resulting from nitrosation of nornicotine via an unknown source of nitrite or nitrogen oxides.…”
Section: Discussionmentioning
confidence: 91%
“…Etter et al reported the presence of nornicotine, up to 0.1% of nicotine content, in some refill liquids [33]. This nornicotine could be easily nitrosated in a user’s saliva, stomach, or urine - a scenario which is quite similar to the endogenous formation of NNN in oral nicotine replacement product users, or in the saliva of people who use tobacco products [12;21]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation